A novel telomerase activator suppresses lung damage in a murine model of idiopathic pulmonary fibrosis. - Claude Jourdan Le Saux; Philip Davy; Christopher Brampton; Seema S Ahuja; Steven Fauce; Pooja Shivshankar; Hieu Nguyen; Mahesh Ramaseshan; Robert Tressler; Zhu Pirot; Calvin B Harley; Richard Allsopp (PLoS ONE, 2013)
The emergence of diseases associated with telomere dysfunction, including AIDS, aplastic anemia and pulmonary fibrosis, has bolstered interest in telomerase activators. We report identification of a new small molecule activator, GRN510, with activity ex vivo and in vivo. Using a novel mouse model, we tested the potential of GRN510 to limit fibrosis induced by bleomycin in mTERT heterozygous mice. Treatment with GRN510 at 10 mg/kg/day activated telomerase 2-4 fold both in hematopoietic progenitors ex vivo and in bone marrow and lung tissue in vivo, respectively. Telomerase activation was countered by co-treatment with Imetelstat (GRN163L), a potent telomerase inhibitor. In this model of bleomycin-induced fibrosis, treatment with GRN510 suppressed the development of fibrosis and accumulation of senescent cells in the lung via a mechanism dependent upon telomerase activation. Treatment of small airway epithelial cells (SAEC) or lung fibroblasts ex vivo with GRN510 revealed telomerase activating and replicative lifespan promoting effects only in the SAEC, suggesting that the mechanism accounting for the protective effects of GRN510 against induced lung fibrosis involves specific types of lung cells. Together, these results support the use of small molecule activators of telomerase in therapies to treat idiopathic pulmonary fibrosis.